Control of microbiological safety (Campylobacter spp.) of poultry carcasses during their processing - Родіонова, К. О. (Scientific Progress & Innovations, 2017)
The article presents the results of isolation bacteria the genus Campylobacter while primary poultry processing on poultry processing enterprise. We determined that selected cultures of micro-organisms in cultural-morphological and biochemical properties had typical biological features for Campylobacter jejuni. The level of isolation of C. jejuni from the swab carcasses was 4,49 %, while as in the study of intact caecum – 7,46 % of all studied samples. The method to improve sanitary-hygienic condition of water in the bath for cooling carcasses that are guaranteed to prevent cross contamination of raw meat pathogenic and conditionally pathogenic microorganisms was developed on the basis of bacteriological researches.